The Spatial Organization of Cities: Deliberate Outcome or Unforeseen Consequence? - Alain Bertaud (University of California, Institute of Urban and Regional Development (IURD), 2004)
Urban spatial structures are shaped by market forces interacting with regulations, primary infrastructure investments and taxes. They are usually the unintended result of unforeseen consequences of policies and regulations that were designed without any particular spatial concerns. However, different urban spatial organizations perform differently. For instance, some urban shapes are unfavorable to the development of public transport; others tend to increase the efficiency of public transport while reducing residential floor consumption. Urban spatial structures are very resilient and they evolve only very slowly. For this reason, a city's spatial structure significantly reduces the range of available development options.
Keywords: 330; Stadtgeographie